The molybdate-binding protein ModA is required for Proteus mirabilis-induced UTI - Huang, Yi; Chen, Jinbin; Jiang, Qiao; Huang, Nan; Ding, Xin; Peng, Liang; Deng, Xiaoyan (Frontiers in Microbiology, 2023)
Background: Proteus mirabilis is one of the pathogens commonly causing urinary tract infections (UTIs). The molybdate-binding protein ModA encoded by modA binds molybdate with high affinity and transports it. Increasing evidence shows that ModA promotes the survival of bacteria in anaerobic environments and participates in bacterial virulence by obtaining molybdenum. However, the role of ModA in the pathogenesis of P. mirabilis remains unknown. Results: In this study, a series of phenotypic assays and transcriptomic analyses were used to study the role of ModA in the UTIs induced by P. mirabilis. Our data showed that ModA absorbed molybdate with high affinity and incorporated it into molybdopterin, thus affecting the anaerobic growth of P. mirabilis. Loss of ModA enhanced bacterial swarming and swimming and up-regulated the expression of multiple genes in flagellar assembly pathway. The loss of ModA also resulted in decreased biofilm formation under anaerobic growth conditions. The modA mutant significantly inhibited bacterial adhesion and invasion to urinary tract epithelial cells and down-regulated the expression of multiple genes associated with pilus assembly. Those alterations were not due to anaerobic growth defects. In addition, the decreased bacteria in the bladder tissue, the weakened inflammatory damage, the low level of IL-6, and minor weight change was observed in the UTI mouse model infected with modA mutant. Conclusions: Here, we reported that in P. mirabilis, ModA mediated the transport of molybdate, thereby affecting the activity of nitrate reductase and thus affecting the growth of bacteria under anaerobic conditions. Overall, this study clarified the indirect role of ModA in the anaerobic growth, motility, biofilm formation, and pathogenicity of P. mirabilis and its possible pathway, and emphasized the importance of the molybdate-binding protein ModA to P. mirabilis in mediating molybdate uptake, allowing the bacterium to adapt to complex environmental conditions and cause UTIs. Our results provided valuable information on the pathogenesis of ModA-induced P. mirabilis UTIs and may facilitate the development of new treatment strategies.